Arrestee Drug Abuse Monitoring II in the United States, 2013 (Restricted Use) - Hunt, Dana ([Verlag nicht ermittelbar], 2014)
The Arrestee Drug Abuse Monitoring II, 2013 is a collection of interview and bioassay data provided by over 3000 arrestees from five county sites within the United States. Under the sponsorship of the Office of National Drug Control Policy (ONDCP), the ADAM II program monitors drug use and related behaviors (treatment experiences, housing stability, drug market activity, age at first use, employment, etc.) in a probability based sample of male adult arrestees within 48 hours of their arrest. The five ADAM II sites for 2013 were: Atlanta, GA (Fulton County and the City of Atlanta); Chicago, IL (Cook County); Denver, CO (Denver County); New York, NY (Borough of Manhattan); and Sacramento, CA (Sacramento County). The 2013 survey represents the seventh year of ADAM II and includes data from 1,900 interviews and 1,681 urine tests that were conducted at the five ADAM II sites over a 21-day period, between May 5, 2013 and July 28, 2013. ADAM II data include official records, arrestee responses from a 20-minute face-to-face interview, and results from voluntary urine samples which tested for the presence of nine different drugs. Identifying information on the arrestees was not retained or shared with law enforcement. Demographic variables include age, gender, race, citizenship, marital status, arrest date and time, county of arrest, number and type(s) of offense(s), education, work status, and language of interview.